ANALISIS KONDISI PSIKOSEKSUAL TOKOH WARAS DALAM NOVEL TRILOGI RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Mujihadi, Mujihadi (Universitas Negeri Surabaya, 2016)
An analysis in novel of trilogy Ronggeng Dukuh Paruk (RDP) written by Ahmad Tohari focuses on how psychosexual which happen in Waras as the character. This research uses descriptive qualitative method. The purpose of this research is to describe the Waras’ psychosexual as the character in the novel which is use the psychological art approach. Psychological art approach is an analysis which focuses on the psychological theory. This analysis model in this novel basically focuses on objective approach. The data in this research is taken from the quotation from the novel RDP which is suitable with research points. After doing the analysis, writer found the psychosexual from the waras as the character. The condition of Waras’ psychosexual if related to the Sigmund freud psychosexual development theory, it can be concluded that that psychosexual of Waras was not in appropriate psychosexual development. These psychosexual problems in Waras as character that in his seventeen he still like playing with the younger children, he also like taking care of podang bird just like younger children, and he also is not interested with women.